Nitric Oxide Detoxification Systems Enhance Survival of Neisseria meningitidis in Human Macrophages and in Nasopharyngeal Mucosa - Stevanin, TÂnia M. (American Society for Microbiology, 2005)
Nitric oxide (NO) contributes to mammalian host defense by direct microbicidal activity and as a signaling molecule of innate immune responses. Macrophages produce NO via the inducible NO synthase (iNOS). The genome of Neisseria meningitidis includes two genes, norB (encoding nitric oxide reductase) and cycP (encoding cytochrome c′), both of which detoxify NO in pure cultures of N. meningitidis. We show here that norB, and to a lesser extent cycP, enhance survival of N. meningitidis within primary human macrophages. Furthermore, accumulation of lysosome-associated membrane protein 1 (LAMP-1) is modified in phagosomes containing an isogenic norB mutant of N. meningitidis compared to the wild type. The survival enhancement conferred by norB and cycP is ablated by pretreatment of macrophages with the nitric oxide synthase inhibitor N(G)-monomethyl-l-arginine (L-NMMA). Despite this evidence that NO detoxification confers advantage, we find, using a highly sensitive chemiluminescence technique, that human macrophage-associated [NO] is low even after activation by lipopolysaccharide and interferon alpha. Furthermore, wild-type N. meningitidis further depletes cell-associated NO during phagocytosis by an active mechanism and survives relatively poorly in the presence of L-NMMA, suggesting that the wild-type organism may utilize NO for optimal survival during intracellular life. The natural habitat of N. meningitidis is the human nasopharynx. Using a nasopharyngeal mucosa organ culture system, we show that mutants lacking norB and cycP also survive poorly in nasopharyngeal tissue compared to wild-type N. meningitidis. These findings indicate that the meningococcus requires active NO detoxification systems for optimal survival during experimental nasopharyngeal colonization and processing by human phagocytic cells.